2005
DOI: 10.1007/s00277-005-1023-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood mononuclear cells and platelets have abnormal fatty acid composition in homozygous sickle cell disease

Abstract: Leukocyte adhesion to vascular endothelium contributes to vaso-occlusion and widespread organ damage in sickle cell disease (SCD). Previously, we found high expression of the adhesion molecules alphaMbeta2 integrin and L-selectin in HbSS individuals with severe disease. Since membrane n-6 and n-3 polyunsaturated fatty acids modulate cell adhesion, inflammation, aggregation and vascular tone, we investigated the fatty acid composition of mononuclear cells (MNC) and platelets of HbSS patients in steady state (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 35 publications
4
22
0
Order By: Relevance
“…As dietary supplements, omega-3 fatty acids are beneficial in many cardiovascular diseases [27;37;38;41;49]. In addition, Ren et al [5658] demonstrated that humans with SCD have decreased omega-3 fatty acids and increased arachidonic acid (an omega-6 fatty acid) in the RBC membrane. To date, trials in humans with SCD have indicated that dietary supplementation with omega-3 fatty acids may reduce severe anemia, vaso-occlusive pain episodes, white blood cell count, and prothrombotic activity [18;52;64].…”
Section: Introductionmentioning
confidence: 99%
“…As dietary supplements, omega-3 fatty acids are beneficial in many cardiovascular diseases [27;37;38;41;49]. In addition, Ren et al [5658] demonstrated that humans with SCD have decreased omega-3 fatty acids and increased arachidonic acid (an omega-6 fatty acid) in the RBC membrane. To date, trials in humans with SCD have indicated that dietary supplementation with omega-3 fatty acids may reduce severe anemia, vaso-occlusive pain episodes, white blood cell count, and prothrombotic activity [18;52;64].…”
Section: Introductionmentioning
confidence: 99%
“…Studies done on the effect of alternative dietary lipid therapy showed that supplementation with N-3 fatty acid exerted a positive benefit on blood viscosity, platelet count, fibrinogen and fatty acid composition of red blood cells and platelets. [11][12][13] Anthropometric measurements can easily reflect changes in the lipid deposition in the human body. Study shows that total cholesterol (TC), low density lipoprotein (LDL) and triglyceride (TG) increase with age and body mass index BMI 14 .…”
Section: Introductionmentioning
confidence: 99%
“…This abnormality, which was evident in the inner and outer leaflets of the lipid bilayer, was manifested primarily by an increase in arachidonic acid (AA, 20:4n-6) and a concomitant decrease in the omega-3 fatty acids, eicosapentaenoic (EPA, 20:5n-3), and docosahexaenoic (DHA, 22:6n-3). Perhaps, more surprisingly, the mononuclear cells and platelets of the patients, although not affect directly by the genetic defect, had the same fatty acid abnormality as the red blood cells (Figure 27.1).Therefore, it appears that the high omega-6 and low omega-3 fatty acids of blood cells is a peculiar biochemical feature of the disease and unlikely to be a reflection of nutritional intake (Connor et al, 1997;Daak et al, 2011;Manodori et al, 2000;Ren et al, 2005bRen et al, , 2006.…”
Section: Blood Cell Membrane Fatty Acid Compositionmentioning
confidence: 99%
“…Moreover, there is evidence that platelets and mononuclear cells of patients with the disease have defective phospholipid fatty acid composition (Ren et al, 2005b). These abnormalities are thought to play a significant role in the pathophysiology and clinical severity of the disease (Hebbel, 1991).…”
Section: Cell Membrane Defect In Scdmentioning
confidence: 99%
See 1 more Smart Citation